Ekstraksi Gelatin Sisik Ikan Nila (Oreochromis spp.) dengan Variasi Konsentrasi Asam Sitrat dan Waktu Demineralisasi - Siti Nur Mufida; Nuniek Herdyastuti (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
The high consumption of tilapia in the community can cause a large amount of tilapia scale waste to be produced. The fish scale waste can still be utilized by further processing into gelatin. Gelatin is acquired through partial hydrolysis of collagen protein found in fish scales. This study aims to find out the difference effect of citric acid concentration and demineralization time on the amount of tilapia scale gelatin. The methods used to obtain gelatin are degreasing, demineralization, extraction, drying, and milling. Gelatin quality testing includes yield, water, ash, pH, and functional groups. The identification of gelatin functional groups was carried out using the PerkinElmer Spectrum IR ES Version 10.6.2. instrument. The variation in the concentration of citric acid added was 1,5 – 6% and the demineralization time was 12 – 72 hours. Outcomes of the most gelatin was produced at a concentration of 6% citric acid and a demineralization time of 72 hours. The resulting yield is 3.84%, water is 8.58%, as is 1.44%, pH is 4.5, and has O-H, N-H, O-H bending, and C=O functional groups which has similarities with commercial gelatin. Itcan conclude that the best gelatin is produced with a concentration of 6% citric acid with a demineralization time of 72 hours.